Savings, Growth and Capital Markets Imperfections : The Case of Borrowing Constraints - De Gregorio, Jose (IMF Working Papers; Working Paper ;, 1993)
This paper studies the effects that borrowing constraints have on savings and growth and argues that, though they increase savings, their effect on growth is ambiguous. Empirical evidence on the extent of borrowing constraints as well as savings, investment, human capital accumulation and growth performance for industrialized countries is presented. A simple model to show the effects of borrowing constraints on savings is developed. Then the model is extended to analyze the effects of borrowing constraints on human capital accumulation and growth. It is shown that borrowing constraints increase savings, but reduce human capital accumulation.